1998
DOI: 10.1038/sj.mp.4000399
|View full text |Cite
|
Sign up to set email alerts
|

A study of chromosome 4p markers and dopamine D5 receptor gene in schizophrenia and bipolar disorder

Abstract: There are several lines of evidence which suggest that chromosome 4p may contain a major susceptibility locus for the functional psychoses. We previously reported a family (family 50) with cases of schizophrenia and schizoaffective disorder which gave maximum lod scores of 1.96 and 1.84 respectively with the markers D4S403 and a microsatellite near to DRD5 (DRD5-M). More recently Blackwood and co-workers described a family segregating bipolar and unipolar affective disorders which gives a maximum lod score of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 21 publications
2
42
0
1
Order By: Relevance
“…4p16, 8p22, 10p14, 13q32, 18p11 and 22q11-13. [4][5][6][7] Several studies have suggested linkage of especially SZ but also BPD to a number of regions on chromosome 22. 8 This has been supported by meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…4p16, 8p22, 10p14, 13q32, 18p11 and 22q11-13. [4][5][6][7] Several studies have suggested linkage of especially SZ but also BPD to a number of regions on chromosome 22. 8 This has been supported by meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, problems with incomplete penetrance, locus heterogeneity and an insufficient number of reliable meioses likely account for the inability to replicate and extend the results. Recent large-scale genetic linkage studies of bipolar disorder using non-parametric, allele-sharing methods have identified several interesting chromosomal regions including 4p16, 6,7 12q23-24, [8][9][10][11] 21q22, [12][13][14][15] 18q21, 16,17 18q22 18,19 and the centromere of 18. 20 Although it is premature to draw any conclusions about these reported linkages until gene(s) for bipolar disorder are identified, several general observations can be made: no finding replicates in all data sets, the effect sizes are small, statistical significance has not reached genome-wide levels, and the regions identified are large (generally Ͼ20 cM) and difficult to approach by positional cloning.…”
Section: Introductionmentioning
confidence: 99%
“…11 Linkage between D4S394 (4p16.1) and bipolar affective disorder was initially reported by Blackwood et al 4 Other surveys have provided additional evidence for linkage of bipolar affective disorder or schizophrenia to markers in this region and other regions on chromosome 4. [5][6][7][8][9] There are, however, also negative reports of linkage of bipolar affective disorder or schizophrenia to chromosome 4. 9,[19][20][21] When considering bipolar patients, two segments (D4S394-D4S2983 and D4S2923-D4S2928-D4S1582) at 4p16.1 received some support (Table 1).…”
mentioning
confidence: 99%
“…1,2 The two disorders may share genetic and nongenetic risk factors. 3 Significant linkage of markers to 4p16 has been found in several families segregating for bipolar disorder or schizophrenia, [4][5][6][7][8][9] which makes this a candidate region for susceptibility gene(s). Perhaps the most interesting candidate gene in this region is the gene coding for the dopamine type 5 receptor (DRD5), 10 as malfunction of the dopamine system has been implicated in psychotic disorders.…”
mentioning
confidence: 99%